2012
DOI: 10.1016/j.mayocp.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Predictors of Serious Neurologic Causes of Dizziness in the Emergency Department

Abstract: Objective: To describe the rate and predictors of central nervous system (CNS) disease in emergency department (ED) patients with dizziness in the modern era of neuroimaging. Patients and Methods: We retrospectively reviewed the medical records of all adults presenting between January 1, 2007, and December 31, 2009, to an academic ED for a primary triage complaint of dizziness, vertigo, or imbalance. The final diagnosis for the cause of dizziness was independently assigned by 2 neurologists, with a third neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
88
6
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 19 publications
12
88
6
12
Order By: Relevance
“…A single‐center study found that 11% of ED visits related to complaints of vertigo or dizziness (Lammers et al., 2011). Isolated vertigo or dizziness can be symptoms preceding posterior circulation stroke or the only symptom of cerebral infarction, results of other studies found that among patients with isolated vertigo or dizziness, about 0.7%–10% are due to acute cerebral infarction (Doijiri, Uno, Miyashita, Ihara, & Nagatsuka, 2016; Kerber, Brown, Lisabeth, Smith, & Morgenstern, 2006; Mosarrezai et al., 2012; Navi et al., 2012; Paul, Simoni, & Rothwell, 2013). In the present study, we found a diagnosis of cerebral infarction among 46/273 (16.8%) hospitalized patients presenting acutely to ED with isolated vertigo or dizziness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single‐center study found that 11% of ED visits related to complaints of vertigo or dizziness (Lammers et al., 2011). Isolated vertigo or dizziness can be symptoms preceding posterior circulation stroke or the only symptom of cerebral infarction, results of other studies found that among patients with isolated vertigo or dizziness, about 0.7%–10% are due to acute cerebral infarction (Doijiri, Uno, Miyashita, Ihara, & Nagatsuka, 2016; Kerber, Brown, Lisabeth, Smith, & Morgenstern, 2006; Mosarrezai et al., 2012; Navi et al., 2012; Paul, Simoni, & Rothwell, 2013). In the present study, we found a diagnosis of cerebral infarction among 46/273 (16.8%) hospitalized patients presenting acutely to ED with isolated vertigo or dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis reviewed 907 case of dizziness visited in emergency department (ED) and found 37 cases (4%) were vascular origin. The vascular dizziness were associated with age >60 years old, accompanying imbalance and focal neurological deficits (Navi et al., 2012). Researches also suggested that vertebral artery hypoplasia, posterior circulation stenosis, and diabetes were correlated with stroke (Mosarrezai, Toghae, Majed, & Aloosh, 2012; Zhang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Rapid, accurate diagnosis of stroke is important to initiate acute treatments and monitor patients to prevent complications. 7 For example, missed cerebellar stroke at the initial ED visit may confer up to an eightfold increased risk of death.…”
mentioning
confidence: 99%
“…SBP ²150 and DBP ²85 were entered into the multivariate logistic regression analysis because they were derived by the ROC curve analysis in the present study, and age ²60 years because it has been shown to be a predictive of stroke in other studies. 15 Ikeda brain structures relate to a system-mediating pressor response close to the cerebellum. 17 It may therefore be possible to assume that DBP in stroke cases is higher than in non-stroke cases; indeed, all our stroke cases included a cerebellar lesion.…”
Section: Discussionmentioning
confidence: 99%